Liraglutide Reduces Vascular Damage, Neuronal Loss, and Cognitive Impairment in a Mixed Murine Model of Alzheimer’s Disease and Type 2 Diabetes - Carranza-Naval, Maria Jose; del Marco, Angel; Hierro-Bujalance, Carmen; Alves-Martinez, Pilar; Infante-Garcia, Carmen; Vargas-Soria, Maria; Herrera, Marta; Barba-Cordoba, Belen; Atienza-Navarro, Isabel; Lubian-Lopez, Simon; Garcia-Alloza, Monica (Frontiers in Aging Neuroscience, 2021)
Alzheimer´s disease (AD) is the most common form of dementia and epidemiological studies support that type 2 diabetes (T2D) is a major contributor. The relationship between both diseases and the fact that AD does not have a successful treatment support the study of antidiabetic drugs to limit or slow down brain complications in AD. Among these, liraglutide (LRGT) is a glucagon-like peptide-1 agonist, currently tested in AD patients in the ELAD (Evaluating Liraglutide in Alzheimer's Disease) clinical trial. However, the effects of LRGT on brain pathology, when AD and T2D coexist, have not been assessed. We have administered LRGT (500 µg/Kg/day) to a mixed murine model of AD and T2D (APP/PS1xdb/db mice) for 20 weeks. We have evaluated metabolic parameters as well as the effects of LRGT on learning and memory. Postmortem analysis included assessment of brain amyloid-β and tau pathologies, microglia activation, spontaneous bleeding and neuronal loss, as well as insulin and insulin-like growth factor 1 receptors. LRGT treatment reduced glucose levels in diabetic mice (db/db and APP/PS1xdb/db) after 4 weeks of treatment. LRGT also helped to maintain insulin levels after 8 weeks of treatment. Whereas we did not detect any effects on cortical insulin or insulin-like growth factor 1 receptors m-RNA levels, LRGT significantly reduced brain atrophy in db/db and APP/PS1xdb/db mice. LRGT treatment also rescued neuron density in APP/PS1xdb/db mice in the proximity (p=0.008) far from amyloid plaques (p<0.001). LRGT reduced amyloid plaque burden in APP/PS1 animals (p<0.001) as well as oligomeric amyloid-β levels (p=0.046) and tau hyperphosphorylation (p=0.009) in APP/PS1xdb/db mice. Spontaneous bleeding was also ameliorated in APP/PS1xdb/db animals (p=0.012) and microglia burden was reduced in the proximity of amyloid plaques in APP/PS1 and APP/PS1xdb/db mice (p<0.001) while microglia was reduced in areas far from amyloid plaques in db/db and APP/PS1xdb/db mice (p<0.001). This overall improvement helped to rescue cognitive impairment in AD-T2D mice in the new object discrimination test (p<0.001) and the Morris water maze (p<0.001). Altogether, our data support the role of LRGT to reduce associated brain complications when T2D and AD occur simultaneously, as regularly observed in the clinical arena.